THE ACTIVITIES OF WOMEN OF THE SOVIET ERA - Malikaxon Qaxramon qizi (American Journals, 2023)
This article discusses the role of women in the Soviet era and their position in the world of politics. The article also contains information about women who were leaders of the Soviet era.
Keywords: gender equality during the Soviet era, female leaders, assistants, school principals, women's place.